1981
DOI: 10.1111/j.1399-3011.1981.tb02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Porcine Elastase Ii by Chicken Ovoinhibitor

Abstract: Interaction o f porcine elastase II with native and modified chicken egg-white ovoinhibitor was studied by determining the residual activity of the partially inhibited enzyme and by direct measurement of the stoichiometry of interaction using affinity chromatography, electrophoresis and gel filtration. It was found that the chymotrypsin binding site that is not modified by mild oxidation with N-chlorosuccinimide (Shechter et al., Biochemistry, (1977) 16,[992][993][994][995][996][997] is capable o f binding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Each domain contains an inhibitory site. Ovoinhibitor has been shown to be active against a large spectrum of serine proteases such as trypsin (Strechter et Berger, 1967;Galzie et al 1996), chymotrypsin and elastase (ScottTomimatsu et al, 1966;feeney, 1971;Gertier and Feinstein, 1971;Vered et al, 1987Vered et al, , 1981.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Each domain contains an inhibitory site. Ovoinhibitor has been shown to be active against a large spectrum of serine proteases such as trypsin (Strechter et Berger, 1967;Galzie et al 1996), chymotrypsin and elastase (ScottTomimatsu et al, 1966;feeney, 1971;Gertier and Feinstein, 1971;Vered et al, 1987Vered et al, , 1981.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Ovoinhibitor (OIH) is a Kazal-type serine inhibitor. It is the main protease inhibitor found in the chicken plasma, and known to inhibit the activity of trypsin, chymotrypsin, and elastase (Zahnley, 1975;Shechter et al 1977;Vered et al, 1981). OIH is a three-domain protein and shares its structure with the ovomucoid protein (Moore et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However a few years later, it was reported by Ardelt (1 1 , 12) that an additional pancreatic endopeptidase with chymotrypsin-like specificityelastase I1 -is also capable of solubilizing elastin. We have further purified, characterized (13, 14) and partially sequenced (15) this enzyme. It was confirmed that in spite of the completely different specificity towards synthetic substrates, both enzymes hydrolyze and solubilize elastin.…”
mentioning
confidence: 99%